Carbon isotope values of hazelnut shells: a new proxy for canopy density - Styring, Amy K.; Jirdén, Elin; Lagerås, Per; Larsson, Mikael; Sjöström, Arne; Ljung, Karl (Frontiers in Environmental Archaeology, 2024)
Hazel (Corylus avellana) has been abundant in the vegetation of northern and central Europe since the early Holocene and has provided food and materials for humans ever since. Here we use stable carbon isotope (δ13C) values of hazelnut shells to infer woodland openness based on the premise of the “canopy effect”. It is well established that plants growing in dense, shaded forests have lower carbon isotope (δ13C) values than plants growing in open areas. By measuring δ13C values in hazelnuts collected from trees growing in different levels of light intensity, we show that the canopy effect is preserved in hazelnuts and that their δ13C values can be used to infer woodland openness in the past. We apply the method to hazelnuts recovered from sites dated to between the Mesolithic and Iron Age (c. 7000 BCE−1000 CE) in southern Sweden. Our results show that the nuts dated to the Mesolithic were harvested from hazels growing in a range of closed to open settings while nuts from subsequent periods were harvested from progressively more open environments. Given the abundance of hazelnuts recovered from many archaeological contexts, this method has the potential to reconstruct the microhabitats exploited by humans in the past and explore the impact of humans on their environment.